Genomic Insights of Cryobacterium Isolated From Ice Core Reveal Genome Dynamics for Adaptation in Glacier - Liu, Yongqin; Shen, Liang; Zeng, Yonghui; Xing, Tingting; Xu, Baiqing; Wang, Ninglian (Frontiers in Microbiology, 2020)
Glacier is the dominant cold habitat in terrestrial environments, providing a model ecosystem to explore extremophilic strategies and study early lives on Earth. The dominant form of life in glaciers is bacteria. However, little is known about past evolutionary processes that bacteria underwent during adaptation to the cryosphere and the connection of their genomic traits to environmental stressors. Aiming to test the hypothesis that bacterial genomic content and dynamics are driven by glacial environmental stressors, we compared genomes of 21 psychrophilic Cryobacterium strains, including 14 that we isolated from three Tibetan ice cores, to their mesophilic counterparts from the same family Microbacteriaceae of Actinobacteria. The results show that psychrophilic Cryobacterium underwent more dynamic changes in genome content, and their genomes have a significantly higher number of genes involved in stress response, motility and chemotaxis than their mesophilic counterparts (P < 0.05). The phylogenetic birth-and-death model imposed on the phylogenomic tree indicates a vast surge in recent common ancestor of psychrophilic Cryobacterium (gained the greatest number of genes by 1,168) after the division of the mesophilic strain C. mesophilum. The expansion in genome content brought in key genes primarily of the categories ‘cofactors, vitamins, prosthetic groups, pigments’, ‘monosaccharides metabolism’ and ‘membrane transport’. The amino acid substitution rates of psychrophilic Cryobacterium strains are two orders of magnitude lower than those in mesophilic strains. However, no significantly higher number of cold shock genes was found in psychrophilic Cryobacterium strains, indicating that multi-copy is not a key factor for cold adaptation in the family Microbacteriaceae, although cold shock genes are indispensable for psychrophiles. Extensive gene acquisition and low amino acid substitution rate might be the strategies of psychrophilic Cryobacterium to resist low temperature, oligotrophy and high UV radiation on glaciers. The exploration of genome evolution and survival strategies of psychrophilic Cryobacterium deepens our understanding of bacterial cold adaptation.